The Immunomodulatory Activity of Leaves Extract of Gaharu Gyrinops versteegii (Gilg.) Domke on Macrophage Cell of Mice (Mus musculus L.) in vitro - Assyafiya Salwa; Tri Rini Nuringtyas; Lisna Hidayati; Nastiti Wijayanti (BERITA BIOLOGI, 2022)
The immune response is divided into innate immune response and adaptive immune response. Macrophages are one of the immunity cells that work both in innate and adaptive immune response. The activities of secondary metabolites present in agarwood-producing plants allow the potential for natural immunomodulators so that the purpose of this study was to determine the potential G. versteegii extract leaves as immunomodulator and to examine the effect of G. versteegii leaves extract toward macrophage cells of mice (Mus musculus L.). The steps to be carried out in this study were the preparation of G. versteegii leaves extract with multi-level extraction, collection of M. musculus, cytotoxicity test with MTT assay, phagocytosis activity test of macrophages calculated by light microscopy (400X), and Griess assay for NO production of macrophages. The cytotoxicity test resulted an IC50 value of G. versteegii leaves extract was 183.45 µg/mL and the Imboost® as comparison solution is 20.12 µg/mL. This value used to determine the concentration of extract for phagocytosis activity test and NO production of macrophages test. The results showed that G. versteegii leaves extract has the potential as an immunomodulator and extract with 20 µg/mL concentration has the highest effect on phagocytosis activity and NO production.